Legal Guarantees and Legal Protection Practices on the Constitutional Rights of Indonesian Migrant Workers - Windi Arista; Joni Emirzon; Mada Apriandi (Journal of Governance, 2022)
The flow of Indonesian labour migration abroad is increasing day by day. This is due to unresolved domestic labour problems. The 2000 International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families is the most significant international human rights document addressing the human rights of migrant workers. The legal problem highlighted in this article is how constitutional rights of Indonesian Migrant Workers (PMI) are protected by legal assurances and practice. This is a normative legal research project that explains, investigates, and analyzes the legal protection of Indonesian migrant workers' rights overseas. The discussion results show that legal guarantees and legal protection practices for PMI's constitutional rights abroad are pretty good and are considered advanced because they use the migrant worker protection convention as the paramount consideration, although there are still inconsistencies in applying the rules.